Syn-depositional Mesozoic siliciclastic pathways on the Moroccan Atlantic margin linked to evaporite mobilisation. (June 2021) - Charton, Rémi; Kluge, Christian; Fernández-Blanco, David; Duval-Arnould, Aude; Bryers, Orrin; Redfern, Jonathan; Bertotti, Giovanni
Abstract: Evaporite mobilisation in evaporite-cored anticlines leads to topographic growth that can alter sedimentary routing in shallow marine environments. This paper analyses two evaporite-cored anticlines perpendicular to the NW Africa coast to understand how their tectonic evolution influenced sediment pathways during the Early to Middle Jurassic and Early Cretaceous exhumation of the Mesozoic margin hinterland. The Essaouira-Agadir Basin in Morocco underwent evaporite deposition during the Atlasic and Atlantic rifting. Subsequent loading and tectonics resulted in re-mobilisation and generation of a variety of evaporite structures. Structural data obtained from analysis of Google Earth images processed using Move 2D allowed derivation of the thickness of sedimentary units on both flanks of the structures. Integrated with sedimentary logs from nine locations around evaporite-cored structures and two onshore wells, this data constrains the depositional record and allow an assessment of siliciclastic flux in the Essaouira-Agadir Basin. The results show the importance of syn-sedimentary evaporite tectonics on basin morphology, which influences the distribution of clastics delivered by fluvial systems and deepwater processes into the basin. This paper constrains the evolution of the Amsittène and Imouzzer anticlines in the Early to Middle Jurassic and support that their growth is associated with halokinesis. Mesozoic syn-sedimentary fold growth would have provided an important control on sediment discharge pathways and on the location of sediment entry points on the shelf margin, that ultimately fed deep water fan systems. This knowledge is key to predict the reservoir presence on the eastern margin of the Central Atlantic Ocean and to some extent, its conjugate margin in Nova Scotia. Highlights: We illustrate a workflow to assess when present-day evaporite-cored anticlines were formed using Google Earth data. The case study selected here is the Essaouira-Agadir Basin where two large anticlines are investigated. Results show that evaporite mobilisation was already active during the Early to Middle Jurassic. As a consequence of early fold growth, the anticlines controlled the sediment pathways of eroded material. The location of Jurassic to Lower Cretaceous deep-sea fans is dependent on that of evaporite-cored anticlines.